2022
DOI: 10.1038/s41598-022-13443-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated mucormycosis in Assiut University Hospitals: a multidisciplinary dilemma

Abstract: Mucormycosis is a life-threatening opportunistic angioinvasive fungal infection. We aimed to describe the frequency, presentations, predictors, and in-hospital outcome of mucormycosis patients in the scope of CoronaVirusDisease-19 (COVID-19) during the third viral pandemic wave. This cross-sectional retrospective study included all patients who fulfilled the criteria of mucormycosis with concurrent confirmed covid19 infection admitted to Assuit University Hospital between March 2021 and July 2021. Overall, 433… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Poorly controlled diabetes and diabetic ketoacidosis have been linked to an increased risk of mucormycosis in COVID-19 patients [ 48 ].Free,unbound iron in the serum also contributes to mucormycosis development in addition to uncontrolled hyperglycemia. Higher levels of serum-free iron have been linked to acidosis and proton-mediated displacement of ferric iron from transfer in diabetic ketoacidosis, both of which are major risk factors for mucormycosis [ 49 ].Also, Moorthy et al [ 50 ] concluded that there is a significant increase in the incidence of maxillofacial fungal infections in patients with diabetes treated for SARS-CoV-2, with a strong association with corticosteroid administration. Neutropenia, malignancy, organ transplant, immunosuppression, and chemotherapy are all risk factors for opportunistic fungal infection [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorly controlled diabetes and diabetic ketoacidosis have been linked to an increased risk of mucormycosis in COVID-19 patients [ 48 ].Free,unbound iron in the serum also contributes to mucormycosis development in addition to uncontrolled hyperglycemia. Higher levels of serum-free iron have been linked to acidosis and proton-mediated displacement of ferric iron from transfer in diabetic ketoacidosis, both of which are major risk factors for mucormycosis [ 49 ].Also, Moorthy et al [ 50 ] concluded that there is a significant increase in the incidence of maxillofacial fungal infections in patients with diabetes treated for SARS-CoV-2, with a strong association with corticosteroid administration. Neutropenia, malignancy, organ transplant, immunosuppression, and chemotherapy are all risk factors for opportunistic fungal infection [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another indirect connection between the concomitant rise in COVID-19 and mucormycosis is the proliferation of fungal spores in the water used in oxygen humidifiers. In hospital water, fungi such as Mucorales can grow and reproduce [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid dosage was significantly higher among patients with mucormycosis. In this center, 90% of patients died due to mucormycosis ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 infection fosters an environment that is favorable to mucormycosis and becomes more prevalent in patients who are battling or recovering from COVID-19 [ 40 ]. Humans can contract two different types of mucormycosis infection.…”
Section: Fungal Infections In Covid-19 Patientsmentioning
confidence: 99%